Adaptive e‐learning platforms can improve student performance and engagement in dental education. Issue 7 (7th April 2021) - Yakin, Muhammed; Linden, Kelly
Abstract: Purpose: Knowledge of normal tissue architecture is essential for one of the vitally important graduate competencies in dentistry, which is the recognition and appropriate referral of patients with oral mucosal and jawbone abnormalities for timely management and improved outcomes. The aim of this study was to examine the effect of online adaptive lessons on improving perceived and measured student performance, motivation, and student perceptions in dental education. Methods: This mixed‐method study was conducted on year 1 and year 3 undergraduate dental students. Adaptive lessons supplementing a number of histology topics were designed and made available. Adaptive lesson scores and analytics, exam scores on topics that were supplemented by adaptive lessons (Experimental Questions), and those that were not (Control Questions) were compared among the year 1 students ( n = 43). A validated questionnaire including Likert‐type scales about the student attitudes and perceptions toward adaptive lessons followed by open‐ended questions was administered to year 1 and 3 students ( n = 57). Results: Students obtained significantly higher scores in experimental exam questions than control exam questions ( p = 0.01). A significantly larger number of students perceived that the adaptive lessons improved their knowledge of the subject ( p < 0.001). Conclusions: The adaptive lessons employed in this study showed significant potential to improve student engagement, motivation, perceived knowledge, and measured exam performance. These are particularly important findings especially amid the COVID‐19 pandemic as institutions transitioned to online education in lieu of face‐to‐face classes to comply with recommendations from Health Authorities.